Inteksi famili x lokasi pada uji keturunan generasi kedua acacia mangium di sumatera dan kalimantan - Teguh Setyaji (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2013)
The study was conducted to investigate the existence of family × site interactions observed in second generation open-pollinated progeny test of Acacia mangium in two locations: Lipatkain, Riau (Sumatra) and Kenangan, East Kalimantan. The progeny tests were established using 51-55 families originated from Oriomo River Papua New Guinea provenance. There were 31common families tested at the both sites. Growth on both sites was significantly different between families. The average height and diameter was 15,9 m and 13,3 cm respectively at Kenangan, and 17,0 m and 16,6 cm respectively at Lipatkain. Family × site interactions were highly significant for height and diameter. The ratio of variance component of interaction to the family variance component (s2fl / s2f ) for diameter (1,6) and height (1,2) were largerr than Shelbourne’s critical value (0,5), indicating the low genotypic stability at family level for the both traits where the diameter was more sensitive than height to changing site conditions. Genetic correlations between the same trait at different sites were low: 0.45 for height and 0.38 for diameter. The greatest genetic gain and relative efficiency of family selection were generally expected from selecting and planting families in the same site.